Epidemics, leprosy, and hope in Graham Greene’s A Burnt-Out Case - Chang, Hawk (Penerbit Universiti Kebangsaan Malaysia, 2024)
Graham Greene is a critically acclaimed British novelist in twentieth-century literature. In his epidemic narrative A Burnt-Out Case (1977), Querry, a world-famous European architect, loses his faith in work and the Catholic religion and escapes to the leprosy-infected Congo. Querry’s ennui makes him a de facto spiritual leper. Such an analogy often demonizes disease and normalizes people’s perception of epidemics, simultaneously misrepresenting patients’ various experiences. Nonetheless, the traditional stigmatization imposed on the Other, such as lepers in the Congo, does not merely necessitate the agony of the infected. Rather, epidemics often entail the victim’s epiphany and turn the sufferers’ pain into pleasure and their desperation into inspiration. Querry’s retrieval of faith in life and humanity illustrates this empowerment. This paper argues that epidemics and people’s responses to them alert us to a deconstructive power inherent in contagion. Epidemics are threatening and fearful, but they also enable humans to reexamine their lives and refresh their sympathetic understanding of human suffering. G. Greene’s (1977) A Burnt-Out Case brings forth a timely version of people’s regained humanity through suffering and disease, something urgently needed in the (post-)COVID-19 era.